Investigation of resistin 420 and 62 gene polymorphism in patients with endometrial cancer - Bahar Yuksel Ozgor; Cem Iyibozkurt; Ercan Bastu; Sinan Berkman; Onay Yalcın; Bedia Cakmakoglu; Halil Saygılı (Elsevier, 2019)
Objective: We aimed to assess resistin gene polymorphisms, namely 420C > G and 62G > A and their effect on the risk of endometrial cancer (EC). Materials and methods: Between January 2012 and January 2015, of the total of 183 patients diagnosed with EC, 94 patients were enrolled into the study. Patients with diabetes mellitus, hypertension and history of any other cancer were excluded. To identify the importance of nucleotide polymorphism including 420C > G and 62G > A in the resistin gene, 94 healthy volunteers were included as the control group. Results: Among the Resistin 420 gene polymorphism profiles, 420 GC (47.9%) was the most common gene polymorphism in the EC group. Also, the polymorphism of 420 CC (57.7%, p: 0.002) lead the list in the control group followed by the 420GC (37.5%) polymorphism. Resistin 62 gene polymorphism analysis demonstrated that the 62GC polymorphism was significantly more common in the EC group (p < 0.01), while 62 AG (52.9%) was observed most frequently in the control group bringing about a reduction in the risk of EC (p < 0.01, Odds Ratio:0.37). Additionally, the alleles of 420G+ and 62A + were significantly more common in the EC group and the control group, respectively (p:0.02 and p<:0.01). Multivariate regression analysis revealed that the presence of 420G + allele increased the EC risk 1.99 fold while the presence of 62A + allele was shown to decrease the risk of EC (p<:0.01 Odds Ratio:0.038). Conclusion: Our study for the first time had demonstrated that Resistin 420G > C and 62G > A gene polymorphisms play a role in EC development. Keywords: Endometrial cancer, Gene polymorphism, Resistin, SNP